Год и один день: роман / Мэриан Эдвардс - Эдвардс Мэриан (Кружево, 2001)
Экземпляры: ф.18 (2001) / Инвентарный номер: 43139 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Э 18 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44